A new chaotic satellite image encryption algorithm based on a 2D filter and Fisher–Yates shuffling - Naim, M.; Ali Pacha, A. (The Journal of supercomputing, 2023)
This paper proposes a new chaotic satellite image encryption algorithm based on a 2D filter and Fisher–Yates shuffling. To reduce the encryption time and increase the security level in the proposed algorithm, the original image is divided into several blocks, and each block is encrypted using the same steps. Firstly, the vector transformation is applied to the original image to obtain a vector that is divided into several vectors where each one consists of 256 pixels. The obtained vector is transformed into a matrix using a matrix transformation. Afterward, the filtering operation generated by the 1D chaotic map is applied to the transformed matrix, where each pixel is filtered using a different mask filter. Then, the rows and the columns of the filtered matrix are scrambled, where the rows are scrambled by the modern Fisher–Yates shuffling and the columns are scrambled by the classical Fisher–Yates shuffling. The two Fisher–Yates shuffling methods are generated by different two 2D hyperchaotic systems. After that, the obtained scrambled matrix is transformed into a vector. Finally, if the storage vector is less than the original vector, the previous steps are repeated until encrypting the remaining next blocks. If not, the storage vector is transformed into a matrix which is considered the final cipher image. The advantages of the proposed algorithm are: Filtering technique has been used in the cryptography field and a different independent filter is used for every single pixel to improve the efficiency of the algorithm. Moreover, the use of Fisher's principle as a permutation technique in the proposed encryption algorithm is an effective manner. The experimental and analysis results show that the proposed algorithm has good performance in terms of a high level of security, large enough key space, tolerance to single event upsets, and low time complexity.